Eksplorasi Etnomatematika Pada Menara Pandang Teratai Purwokerto - Felisa, Dhea Ika; Raekha Azka (Polynom: Journal in Mathematics Education, 2022)
Purwokerto Lotus View Tower is a new icon of Banyumas Regency located in West Purwokerto area. This research aims to explore ethnomathematics and examine more deeply the mathematical concepts in the Purwokerto Lotus View Tower. The research method used is descriptive qualitative research method with ethnographic approach. Data collection techniques in this research are in the form of literature study, direct observation, and documentation. The results showed that there are elements of ethnomathematics or mathematical concepts in the Purwokerto Lotus View Tower, namely lines, angles, flat buildings, space buildings, and congruence. The elements of mathematics or ethnomathematics concepts contained in the Menara Pandang Teratai Puewokerto can be used as a source of mathematics learning so that the learning process is more interactive and meaningful in the form of introducing the concept of elements of lines, angles, flat buildings, spaces, and congruence.